Surgical Resection of Brain Metastases—Impact on Neurological Outcome - Schödel, Petra (Molecular Diversity Preservation International (MDPI), 2013)
Brain metastases (BM) develop in about 30% of all cancer patients. Surgery plays an important role in confirming neuropathological diagnosis, relieving mass effects and improving the neurological status. To select patients with the highest benefit from surgical resection, prognostic indices (RPA, GPA) have been formulated which are solely focused on survival without considering neurological improvement. In this study we analyzed the impact of surgical resection on the neurological status in addition to overall survival in 206 BM patients. Surgical mortality and morbidity was 0.0% and 10.3% respectively. New neurologic deficits occurred in 6.3% of all patients. The median overall survival was 6.3 months. Poor RPA class and short time interval between diagnosis of cancer and the occurrence of BM were independent factors predictive for poor survival. Improvement of neurological performance was achieved in 56.8% of all patients, with the highest improvement rate seen in patients presenting with increased intracranial pressure and hemiparesis. Notably, the neurological benefits were independent from RPA class. In conclusion, surgical resection leads to significant neurological improvement despite poor RPA class and short overall survival. Considering the low mortality and morbidity rates, resection should be considered as a valid option to increase neurological function and quality of life for patients with BM.